2019
DOI: 10.1016/j.chemosphere.2019.06.115
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated flame retardants in the sediments of the Chinese Yellow Sea and East China Sea

Abstract: Halogenated flame retardants were investigated in the sediments of Yellow and East China Seas. DBDPE was the predominant contaminant and is one order of magnitude higher than BDE 209. High levels of HFRs were found in the depositional zones of the Yellow Sea. HFRs from the Bohai Sea was the major source of HFRs in the Yellow Sea. Yangtze River contributed less HFRs to the sediments of East China Sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Hu et al (2009) also reported high DDTs concentrations around the same area of the BS. Furthermore, a previous study found high levels of HFRs distributed in the depositional zones of the Yellow Sea (YS) (Li et al, 2019). Sediments collected from the Longkou coast and west of Laizhou Bay are also belong to fine silts (4.3e5.5 Ф) (Fig.…”
Section: Distribution Of Dp and Its Influencing Factorsmentioning
confidence: 96%
“…Hu et al (2009) also reported high DDTs concentrations around the same area of the BS. Furthermore, a previous study found high levels of HFRs distributed in the depositional zones of the Yellow Sea (YS) (Li et al, 2019). Sediments collected from the Longkou coast and west of Laizhou Bay are also belong to fine silts (4.3e5.5 Ф) (Fig.…”
Section: Distribution Of Dp and Its Influencing Factorsmentioning
confidence: 96%
“…1C), where the essential path of the current from the LB was located. In addition, the active coastal resuspension intensify in the shallow water induced by winter monsoon, which are the major factors resulting the long-distance transport of the particulates from the Bohai Sea to the Yellow Sea (Qiao et al, 2016;Li et al, 2019). Thus, for areas not strongly affected by production sources, transportation from highly polluted waters through coastal currents or water masses could further aggravate the risk of contamination and lead to widespread pollution in the marine ecosystem.…”
Section: Spatial Variationsmentioning
confidence: 99%
“…[6] However, the flame retardants containing halogen will produce smoke and toxic gases in combustion which are harmful to the human body and environment. [7][8][9] In light of this, preparing a simple and efficient flame retardant is still a promising research direction.…”
mentioning
confidence: 99%